A NIR light triggered disintegratable nanoplatform for enhanced penetration and chemotherapy in deep tumor tissues. (July 2020) - Xiong, Xiang; Xu, Zeng; Huang, Huabei; Wang, Yi; Zhao, Jingya; Guo, Xing; Zhou, Shaobing
Abstract: Poor penetration and resultant low accumulation of nanomedicines in deep tumor tissues greatly reduce the chemotherapeutic efficiency. How to maximize the tumor accumulation is still a great challenge in the development of nanocarriers. Here, we developed a cyclic Arg-Gly-Asp-Phe-Lys peptide (cRGD) modified and near-infrared (NIR) light triggered disintegratable liposomal nanoplatform (PAM/Pt@IcLipo), where photosensitizer indocyanine green (ICG) was loaded in the out layer and polyamindoamine (PAMAM) dendrimers grafting cisplatin prodrug (PAM/Pt) were encapsulated inside. The cRGD ligands render the liposomes to target αv β3 integrin receptors overexpressed by vascular endothelial cells in tumor tissues. Long blood circulation can be achieved owing to the relative large size (~162 nm) of the liposomes. When irradiated by NIR light locally at tumor site, ICG heating detonated the thermosensitive liposomes to release the small sized PAM/Pt nanoparticles (~8.6 nm), which were capable of penetrating into the deep tumor tissue. The in vivo results also showed that the PAM/Pt@IcLipo could significantly improve the penetration of cisplatin drug in deep tumor tissues under NIR light irradiation, resulting in an excellent antitumor activity. This nanoplatform solved the dilemma of long blood circulation of large sized nanoparticles and deep penetration of small sized nanoparticles, opening up a new strategy in the development of nanomedicines for cancer therapy.